Ideational Power or Political Demand? Tracing the Logics of In-Work Benefit Reforms in France and the United Kingdom. - Robertson, Ewan (Political Studies, 2026)
In recent decades, numerous welfare states have implemented in-work benefits to 'make work pay' and tackle in-work poverty. To explain the adoption and institutionalisation of this instrument, studies tend to emphasise either socio-political demand or ideational influences as motivators of policy decisions. However, the relative importance of these causal logics, and the relationship between them, remains ambiguous. To advance this debate, this article examines in-work benefit reforms in two welfare states: France and the United Kingdom. Examining reforms from the late 1990s to the 2010s, findings suggest that policy change and convergence were driven by an ideational rather than a demand-based logic. Reforms were more strongly motivated by the shared interpretive frameworks of policymakers and their instrumental use of ideas (ideational power) rather than the demands of voters and organised interests. This finding on the specific drivers of in-work benefits contributes wider insights into the roles of ideas in public policy.